O USO DE CONCEITOS VETORIAIS EM GEOMETRIA ANALÍTICA NO ENSINO MÉDIO COM O AUXÍLIO DO GEOGEBRA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
To teach Mathematics to highschool students is a big challenge, the traditional classes , for these students used to digital environment, don't arouse much mind and interest. So, the use of technological resourses, as the computer, can be valuable, for the teacher can connect theory to practice and vice versa; involving them in activities that enable a significant learning, stimulating the curiosity. This task has as its goal to propose an alternative approach to the Analitcs Geometry highschool students different from the ones found in the didactic books, so using computer resourses through a sequence of exercises accomplished and provided in the GeogebraBook as tool of dynamics and geometric construction. And it was included the concept of vectors in order to facilitate the understanding of the matter. The proposal was done at state school, located in Itarare, São Paulo; where it was suggested to the final years highschool students a sequence of exercises developed and provided by the GeogebraBook author.Outstanding the importance of the tecnological resourses in the Mathematics teaching and the role of the teacher forefront the technology progress, as agent that facilitates the interdisciplinarity and as knowledge mediator and motivatror.
Keywords: Geometria Analítica; Ensino médio; Vetores e GeogebraBook; Analitics Geometry; Highschool; Vectors and GeogebraBook; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA